Hepatic focal nodular hyperplasia after pediatric hematopoietic stem cell transplantation: The impact of hormonal replacement therapy and iron overload. Issue 4 (30th December 2019) - Cattoni, Alessandro; Rovelli, Attilio; Prunotto, Giulia; Bonanomi, Sonia; Invernizzi, Pietro; Perego, Rosangela; Mariani, Anna Maria; Balduzzi, Adriana
Abstract: Background: The advent of techniques for the assessment of iron overload (liver T2*‐MRI) has led to the awareness that focal nodular hyperplasia (FNH) represents a possible incidental finding after hematopoietic stem cell transplantation (HSCT), though its pathogenesis is still unclear. Methods: We performed a retrospective analysis of the liver T2*‐MRI scans performed between 2013 and 2018 in a single pediatric HSCT Unit and recorded the number of patients with FNH (group A). Patients incidentally diagnosed with FNH at imaging performed for different clinical indications were included in group B. Results: Nine of 105 (8.6%) patients from group A were diagnosed with FNH. Group B included three patients. Overall, 12 patients were diagnosed 4.4 ± 3.1 years after HSCT. At univariate analysis, female gender (odds ratio [OR] 3.77, P = .03), moderate‐to‐severe iron overload (OR 6.97, P = .01), and hormone replacement therapy (HRT) administered for at least 6 months (OR 18.20, P = .0002) exposed patients to a higher risk of developing FNH. The detrimental effect of HRT was significant also at multivariate analysis (OR 7.93, P = .024). MRI‐T2* values in affected patients were statistically lower than healthy controls ( P < .001). Conclusions: We confirm the high incidence of FNH among transplanted pediatric patients and demonstrate the potential pathogenic role of HRT and iron overload.